Exploring e-scooters as first- and last-mile with Gaussian mixture and machine-learning models - Jaewon Han; Hyebin Kim; Sugie Lee (Transportation Research Part D: Transport and Environment, 2026)

Comparison of surface-guided radiotherapy-based deep inspiration breath hold and continuous positive airway pressure techniques in left-sided breast cancer: dosimetric and workflow analysis - Su Chul Han; Jason Joon Bock Lee; Jin Dong Cho; Il Sun Jeong; Heerim Nam; Hyebin Lee (Physical and Engineering Sciences in Medicine, 2026)

Seasonal interplay of water mass mixing and nutrient dynamics in an Arctic fjord: a case study of Kongsfjorden, Svalbard - Hyebin Kim; Dukki Han; Sang Rul Park; Tae-Hoon Kim (Ocean Science, 2025)
This study examined seasonal variations in water mass structure and nutrient dynamics in Kongsfjorden, a high Arctic fjord where water mass composition varies seasonally due to mixing among Atlantic Water, Polar Surface Water, and glacial meltwater. In spring, the dominance of Modified Atlantic Water (MAW) facilitated active vertical mixing, leading to relatively high, uniform nutrient concentrations throughout the water column. In summer, the enhanced influence of glacial meltwater and warmer Polar Surface Waters (PSWw) resulted in strong surface stratification and significant nutrient depletion in the upper layer. To disentangle the effects of physical mixing from biological consumption, theoretical nutrient concentrations were calculated based on a four-component water mass mixing model. The positive differences between theoretical and observed concentrations (ΔNutrient) were indicative of significant biological uptake, which accounted for substantial nutrient reductions in observed surface concentrations from spring to summer: approximately 69 ± 18 % for NOx (sum of nitrate and nitrite; NO3- + NO2-), 74 ± 15 % for phosphate, and 47 ± 18 % for silicate. Crucially, ΔNutrient values served as a “biogeochemical memory”, reflecting the cumulative net biological consumption since the spring bloom rather than just instantaneous phytoplankton biomass. These biological processes also altered nutrient stoichiometry, as reflected by an increase in the surface dissolved inorganic nitrogen to phosphorus (DIN/DIP) ratio (DIN = NO2? + NO3- + NH4+; DIP = PO43-) from 15.0 in spring to 18.8 in summer, indicating a shift in nutrient limitation patterns. Consequently, summer surface waters transitioned toward potential co-limitation, with concentrations of phosphate (∼ 0.13 ± 0.07 µM) and silicate (∼ 1.66 ± 0.39 µM) approaching their respective limitation thresholds. These findings highlight a clear seasonal transition from a physically controlled, nutrient-replete spring to a biologically regulated, nutrient-limited summer. This understanding is crucial for predicting how Arctic fjord ecosystems, and their primary productivity, will respond to ongoing Atlantification and increased freshwater input under climate change.

Filter-assisted sample preparation for on-site detection using a bi-functional linker-based biosensor demonstrated with Escherichia coli O157:H7 - Hyebin Han; Seung Hwan Ham; Youngsang You; Jihae Lee; Jungwoo Hahn; Young Jin Choi (Food Chemistry, 2025)

Production and application of Paenibacillus polymyxa levan as an antiviral priming agent against cucumber mosaic virus infection in tobacco plants - Hyunjun Ko; Hangil Kim; Ji Won Heo; Sangjun Lee; Yongtae Yu; Hyebin Kim; Hyeon-Seok Oh; Chan-Gi Min; Seokmin Baek; Han Suk Choi; Sung Jin Moon; Woohyun Sim; et al. (Carbohydrate Polymers, 2025)